The Grammatical Impact of EFL Arabic Learnersâ€™ Mother Tongue in English Writing of Al-Mergib University Students - Mohamed Wajej, Abdelbaset; Mujiyanto, Januarius (English Education Journal, 2017)
The process of second language learning has been influenced by so many factors, the mother tongue (L1) maybe the one of the greatest factors. When the rules of the two languages contact that is called â€˜language transferâ€™. Two results might be caused when the second language learner tries to recall one of his/her mother tongueâ€™s items: positive transfer or negative transfer. In this study, the researcher focuses on the negative transfer or mother tongue interference in English writing. A big number of linguists have researched the influence and the relationship between L1 and L2 learning. Many studies indicate that for EFL students, there tends to be interference from their first language in the process of writing in English. This paper mainly focuses on some factors of the grammatical, namely subject-verb agreement, tenses, articles and prepositions, influence of L1 â€œArabicâ€ in L2 â€œEnglishâ€ writing learning, and the L1 transfer to English writing. The participants of this study were 22 Libyan third-year students of English Department in Al-Mergib University. In the data collection period, the students were required to write an essay in English and to do fill-the-blanks test then the gathered data were analyzed qualitatively. The findings showed that the participants clearly recalled structures, thought and translated from their mother tongue in their English writing in all the studied items: subject-verb agreement, tenses, articles and prepositions. The students also showed other grammatical errors such as: missing verb to be, use of word order, wrong spelling and plurality case. Teachers then should include more free and controlled writing exercises and should vary their teaching methods to improve students writing abilities.